Numerical and Experimental Study of Air-to-Air Plate Heat Exchangers with Plain and Offset Strip Fin Shapes - Kyung Rae Kim; Jae Keun Lee; Hae Do Jeong; Yul Ho Kang; Young Chull Ahn (Energies, 2020)
This study evaluates the performance of a plate heat exchanger numerically and experimentally. The predictive model for estimating the heat transfer and frictional pressure drop across the plain and offset strip fins is compared with the experimental results with the parameters of Reynolds number and fin pitch. The heat transfer of the offset fin shape is 13.4% higher than that of the plain fin in the experiment in the case of Re = 6112 for the hot airflow and Re = 2257 for the cold airflow. A predictive model uses the effectiveness-Number of Transfer Units (NTU) method with the discretization in the segments divided into small control volumes in the heat exchanger. The difference of heat transfer and pressure drop for the plain fin between the numerical and the experimental results are approximately 1.9% and 5.9%, respectively. Thus, the results indicate that the predictive model for estimating the heat transfer is useful for evaluating the performance of the plate heat exchanger in the laminar-to-transition regions.